Leishmaniasis: The Biology of a Parasite - Díaz López, Emilia; Ponte-Sucre, Alicia (My University, 2018)
One of the main challenges of therapeutic tools for the treatment of parasitic diseases, including leishmaniasis, is the interwinned relationship between therapeutic failure and drug resistance. In fact, some field parasites might be naturally resistant to classical drugs and additionally, current therapies may induce drug resistance. In fact, treatment failure in leishmaniasis has multiple causes. Some are related to drugs, such as pharmacokinetic properties, toxicity, use of sub-optimal doses, or high cost of treatment. Parasite-related grounds include chemo-resistance and tolerance. Last but not least, the host plays a fundamental role in this situation since the patient's immune status and the risk of re-infection if living in an endemic region might also contribute to therapeutic failure. All these features are at least partially responsible for the disappointing persistence and re-emergence of leishmaniasis, as well as its death and disability-adjusted life year toll worldwide. A better understanding of the disease itself and of drug resistance, its molecular basis, its consequences, and the definition of possible paths for better treatments may help improve this depressing picture. In the present volume experts in the field cover current knowledge and future trends of these and many other aspects of drug resistance in Leishmania. This initial chapter offers a general introduction to the biology of the parasite, a piece of information fundamental for the topics included in the book and the comprehension of challenges we currently face for this disease